2021
DOI: 10.51537/chaos.850012
|View full text |Cite
|
Sign up to set email alerts
|

Chaos synchronization in chaotic current modulated VCSELs by bidirectional coupling

Abstract: This paper reports on the synchronization proprieties in bidirectional coupled current modulated vertical cavity surface-emitting lasers (CMVCSELs) based on the combined model of Danckaert et al..Regular pulse packages and chaotic behaviors are found in CMVCSEL during the numerical results. The suitable coupling strength leading to high quality of synchronization is determined by numerical analysis. The consequence of the parameter mismatch and the duration of the synchronization process are also highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Compared to other semiconductor lasers, VCSELs have many attractive peculiarities like: Annular beam contour with confined bifurcation, very low verge current, solitary mode operation, and easy operation [14]. Many works dealing with the dynamics of VCSELs have been investigated in terms of bias current, time delay signature, the complexity of polarization properties, and switching between modes [15][16][17][18][19][20][21]. The study of synchronization of coupled VCSELs revealed the existence of bifurcation cascade, multi-periodic and chaotic oscillations in [22] under the influence of predilection current and coupling force.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other semiconductor lasers, VCSELs have many attractive peculiarities like: Annular beam contour with confined bifurcation, very low verge current, solitary mode operation, and easy operation [14]. Many works dealing with the dynamics of VCSELs have been investigated in terms of bias current, time delay signature, the complexity of polarization properties, and switching between modes [15][16][17][18][19][20][21]. The study of synchronization of coupled VCSELs revealed the existence of bifurcation cascade, multi-periodic and chaotic oscillations in [22] under the influence of predilection current and coupling force.…”
Section: Introductionmentioning
confidence: 99%